Innovative approach for the in vitro research on biomedical scaffolds designed and customized with CAD-CAM technology. (December 2016) - Marrelli, Massimo; Pujia, Antonella; Palmieri, Francesca; Gatto, Roberto; Falisi, Giovanni; Gargari, Marco; Caruso, Silvia; Apicella, Davide; Rastelli, Claudio; Nardi, Gianna Maria; Paduano, Francesco; Tatullo, Marco
Introduction: Studies on biomaterials involve assays aimed to assess the interactions between the biomaterial and the cells seeded on its surface. However, the morphology of biomaterials is heterogeneous and it could be tricky to standardize the results among different biomaterials and the classic plastic plates. In this light, we decided to create, by means of computer-aided design (CAD) technology, a standardized sample model, with equal shape and sizes, able to fit into a classic shape of a 96-wells tissue culture plate (TCP). Methods: The design of this sample consists of a hole in the top in order to allow the injected cells to settle without them being able to slip from the sides of the sample to the bottom of the TCP wells. This CAD project is made using the software Pro-Engineer. The sample will totally fill the wells of the 96-well TCP. Dental pulp stem cells have been used to assess the ability of the different sample to support and promote the cell proliferation. Results: Twelve titanium, 12 gold–palladium, and 12 zirconium oxide customized samples were designed by means of the software cam powermill, by importing the .stl file created in Pro-Engineer software. The proliferation rate of the tested scaffolds showed to be similar to the control in the group with the customized shape. Conclusion: We think that our method can be useful to test different types of scaffolds when a greater accuracy of the measurements is desirable in order to verify the cell behavior of these scaffolds. Our innovative method can improve the standardization process in the evaluation of cell behavior on different biomaterials to open the way to more reliable tests on biomatrices functionalized with drugs or growth factors applied to the future regenerative medicine.